Simulasi Dispersi dan %Fatality Gas Buang SO2 dan CO2 Hasil Pembakaran Low Rank Coal PLTU Independent Power Producer (IPP) Lombok Timur (50 MW) Menggunakan Gaussian Model - Haryandi Haryandi; Shafwan Amrullah; Nurkholis Nurkholis (Dampak, 2021)
The combustion of coal in coal-fired power plants produces air pollution such as SO2, NOx, CO2, and particulates. The Sembelia Coal-Fired Power Plant, located on Sambelia Road, Padak Guar, East Lombok, West Nusa Tenggara, managed by PT. Lombok Energy Dynamic, utilizes 200,000 tons/year of young coal to generate 50 MW of electricity. This poses a significant potential for environmental pollution. This research aims to simulate the potential dispersion of SO2 and CO2 emissions into the environment and the % fatality resulting from the combustion of coal at the Sembelia Coal-Fired Power Plant using the Gaussian Model. The research was conducted through literature review and direct observations at the Sembelia Coal-Fired Power Plant. Subsequently, the study calculated the simulation potential of SO2 and CO2 concentrations for varying distances. At the end of the study, the potential dispersion and % fatality due to SO2 and CO2 emissions were also calculated at four points around the power plant.The research findings indicate that the dispersion of SO2, with a dispersion mass of 0.096 kg/second, increases from 2,000 to 46,000 meters, ranging from 6.876x10^-46 ppm to a concentration of 1.276x10^-5 ppm. Afterward, it decreases to 0 ppm, resulting in a % fatality of 0%. The potential dispersion of CO2 into the environment, with an exit mass of 8.252 kg/second, increases from 2,000 to 58,000 meters, from a concentration of 62.47x10^-63 ppm to a concentration of 7.9x10^-4 ppm. Subsequently, the CO2 concentration decreases to 0 ppm, with a % fatality of 0%. The dispersion calculations at four points around the Sembelia Coal-Fired Power Plant indicate that it is safe from SO2 and CO2 dispersion, resulting in a % fatality of 0%. Keywords: Air Pollution, Coal youth, Gaussian Model, Dispersion Potential, %Fatality ABSTRAK Pembakaran batubara pembangkit listrik tenaga batubara menghasilkan polusi udara seperti SO2, NOx, CO2 dan juga Partikulat. PLTU Sembelia yang berada di Jalan Raya Sambelia, Padak Guar, Lombok Timur, Nusa Tenggara Barat Sambelia yang dikelola oleh PT. Lombok Energy Dinamic menggunakan 200.000 ton/tahun batubara muda untuk menghasilkan 50 MW listrik. Ini bisa menjadi potensi besar pencemaran lingkungan. Penelitian ini bertujuan untuk mensimulasikan potensi dispersi gas buang SO2 dan CO2 ke lingkungan serta %fatality akibat pembakaran batubara PLTU Sembelia menggunakan Gaussian-Model. Penelitian ini dilakukan dengan studi literatur dan observasi langsung ke PLTU Sembelia. Setelah itu, penelitian ini dilakukan dengan menghitung potensi simulasi konsentrasi SO2 dan CO2 untuk variabel jarak. Pada akhir penelitian, perhitungan potensi dispersi dan%fatality oleh gas SO2 dan CO2 juga dihitung pada empat titik di sekitar pembangkit listrik. Hasil penelitian ini adalah dispersi SO2 dengan massa dispersi 0,096 kg/detik dari jarak 2.000 hingga 46.000 m meningkat dari 6,876x10-46 ppm hingga konsentrasi 1,276x10-5 ppm. Setelah itu turun menjadi 0 ppm. % Fatality yang dihasilkan adalah 0%. Dan potensi dispersi CO2 ke lingkungan dengan massa keluar 8,252 kg/detik meningkat pada jarak 2.000 hingga 58.000 m, dari konsentrasi 62,47x10-63 ppm hingga konsentrasi 7,9x10-4ppm. Selanjutnya konsentrasi CO2 berkurang menjadi 0 ppm. %Fatality yang dihasilkan adalah 0%. Untuk perhitungan dispersi di empat titik di sekitar PLTU Sembelia dapat dikatakan aman dari dispersi SO2 dan CO2, dan%fatality yang dihasilkan adalah 0%. Kata Kunci: Polusi udara, batubara muda, Gaussian-Model, Potensi dispersi, %fatality